Researcher Profile: Thomas Smith - Thomas Smith (Journal of Financial Therapy, 2017)
Dr. Thomas E. Smith has been a clinician, researcher, supervisor, and professor for over 30 years. He has more than one hundred articles spanning the fields of family therapy, social work, psychology and financial therapy. He was formerly the Training Director for an accredited postmasters’ training program in family therapy and is now a Professor of Social Work at Florida State University. He is a licensed social worker and a Clinical Fellow and Approved Supervisor with the American Association for Marriage and Family Therapy. He is has written several books on financial therapy. He is the founder and director of the Financial Therapy Center that is affiliated with the College of Social Work at Florida State University.